Formation of futureeducators’tolerancein the inclusive environment - Пономарьова, Г. Ф. (Scientific notes of the pedagogical department, 2019)
The research deals with the study of the issue of thefutureeducators’in inclusive environment formation of tolerance among future educators in the inclusive environment of higher pedagogicaleducational establishmentin the context of solving the complex of problems of inclusive education. It is placed the emphasis on the development of the humanistic potential of the relationship between the subjects of the educational process as a condition for the realization of the humanistic paradigm of education.The inclusive educational environment, which determines the humanistic orientation of the educational process, is characterized. On the basis of theoretical analysis of scientific publications, the results of research on the development of education as an inclusive environment and the formation of tolerance of such people who are its subjects, are summarized. Using comparisons allowed us to trace the development of the concept «tolerance» and find out its current content within the context of researching problem. By the scientific generalization, the notion "tolerance" and the ways of its formation are defined. The expediency of creating an inclusive educational environment in higher pedagogical educational establishmentis substantiated, its main features are mentioned and the importance of tolerant relationships in such environment is emphasized. The key positions of the positive experience of forming tolerance of students in the inclusive educational environment are generalized. Using polling methods and questionnaires, the reasons hindering the development of an inclusive educational environment, and some factors having a positive effect on its formation as anenvironmental of tolerant relationship between subjects are found.